Prevalence and Clinical Characteristics of the Restless Legs Syndrome (RLS) in Patients Diagnosed with Attention Deficit Hyperactivity Disorder (ADHD) in Antioquia (2018)
ABSTRACT: introduction: Attention Deficit Hyperactivity Disorder (ADHD) is the most common behavioral issue for children. One of the sleeping disorders most frequently related to ADHD is the Restless Legs Syndrome (RLS), characterized by an irresistible urge to move the legs, something that is generally associated with paresthesias and motor restlessness. The prevalence rate of RLS in children diagnosed with ADHD is close to 18%, but in Colombia, these cases have been hardly studied. Objective: To determine the frequency of RLS, in children with ADHD. Methods: A cross-sectional study, filled out by parents of children diagnosed with ADHD, were analyzed. This questionnaire contained clinical criteria for classifying ADHD according to the DSM-IV, as well as diagnostic criteria for RLS by the National Institutes of Health (2003). Results: A predominance rate of 65.6% in combined ADHD was observed in children with RLS criteria. Upon carrying out an exploratory data analysis, it was found that having a family history of RLS and belonging to the middle or low socioeconomic strata are conditions associated with the presence of RLS in children with ADHD, with a significant p (p < 0.000) and a PR of 4.47 (3.16-6.32). Conclusions:The prevalence of RLS was similar to the findings of other clinical investigations. However, it highlights new prevalence values in relation to the comorbidity between ADHD and RLS, suggesting the need for new clinical and therapeutic alternatives amidst the presence of both syndromes.